2019
DOI: 10.1002/aenm.201901449
|View full text |Cite
|
Sign up to set email alerts
|

Optical Shading Induces an In‐Plane Potential Gradient in a Semiartificial Photosynthetic System Bringing Photoelectric Synergy

Abstract: and are believed to be key to sustainably overcoming the terawatt energy challenge the world currently faces. [1][2][3] The field of solar energy harvesting, previously dominated by inorganic materials, has in recent times witnessed the rapid ascent of organic materials in device designs. [4] In particular, much of the progress in this field has been driven by bioinspiration with nature's photosynthetic (PS) apparatus as a model material. [5][6][7] The aim of exploiting nature's designs for the harnessing of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…[15] Rba. sphaeroides RCs deposited on nanostructured silver have generated photocurrents up to 416 μA cm À 2 in a conventional biophotoelectrochemical cell, [11] whereas RC-LH1 proteins coupled to photoactive semiconductor materials in solid-state configurations have shown stable photocurrents up to 1.3 mA cm À 2 , [16] and RC-LH1 multilayers suffused with gel electrolytes have shown stable photocurrents up to 850 μA cm À 2 . [17] While these current densities are still an order of magnitude away from those of solar cells made from purely synthetic materials, rapid growth in biophotoelectrode performance is closing this gap.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Rba. sphaeroides RCs deposited on nanostructured silver have generated photocurrents up to 416 μA cm À 2 in a conventional biophotoelectrochemical cell, [11] whereas RC-LH1 proteins coupled to photoactive semiconductor materials in solid-state configurations have shown stable photocurrents up to 1.3 mA cm À 2 , [16] and RC-LH1 multilayers suffused with gel electrolytes have shown stable photocurrents up to 850 μA cm À 2 . [17] While these current densities are still an order of magnitude away from those of solar cells made from purely synthetic materials, rapid growth in biophotoelectrode performance is closing this gap.…”
Section: Introductionmentioning
confidence: 99%
“…Skin-inspired tactile sensors 22,23 have promising applications in humanoid robotics 24 , skin prosthetics 25,26 , body-attachable 27 or on-skin electronic devices 28,29 , and in unobtrusive health monitors 30 . Significant research effort has been devoted to developing smart tactile sensors for varied applications employing different principles of sensing such as capacitive pressure sensing 31,32 , piezoresistivity 33,34 , piezoelectricity 35,36 , piezotronics [37][38][39] , triboelectricity 40 , tribotronics 41,42 and pressure-sensing with field-effect transistors 31,43,44 .…”
Section: Introductionmentioning
confidence: 99%
“…Shadows are cast if the moving object on the top is opaque. Ravi et al reported that it is possible to tune the work function of a metal/semiconductor junction by illuminating light on the junction, resulting in a directional flow of electrons from the bright zone to the dark zone [15][16][17] . Scavenging the illumination contrast that arises on the surface underneath and generating power from this effect is an effective solution to harvest solar energy.…”
mentioning
confidence: 99%